2014
DOI: 10.3341/kjo.2014.28.2.122
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation of Routine Tear Function Tests and Conjunctival Impression Cytology in Dry Eye Syndrome

Abstract: Purpose:To establish the strength of the association between routine tear function tests and conjunctival impression cytology (CIC) and to determine whether they simulate the morphological and cytological changes that occur on the ocular surface in dry eye. What are the sensitivity, specificity and positive predictive values of these tests when CIC is considered the gold standard? Methods: The tear film profile included tear film break up time (TBUT), Schirmer's-1, Rose Bengal scores (RBS), and impression cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
28
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 25 publications
4
28
0
1
Order By: Relevance
“…ICS collects the most superficial layers of the ocular surface due to the adhering property of the sampling device [4]. ICS is now widely used in human ophthalmology to examine the healthy ocular surface [5] and to assess conjunctival and corneal alterations in contact lens wearers [6][7][8] Examination of eyes with ocular surface neoplasia [9,10] and keratoconjunctivitis sicca [11,12] are other indications for ICS. A major advantage of ICS is the arrangement of harvested cells in their natural layout; thus enabling clinical pathologists to examine an exact copy of the area of interest.…”
Section: Introductionmentioning
confidence: 99%
“…ICS collects the most superficial layers of the ocular surface due to the adhering property of the sampling device [4]. ICS is now widely used in human ophthalmology to examine the healthy ocular surface [5] and to assess conjunctival and corneal alterations in contact lens wearers [6][7][8] Examination of eyes with ocular surface neoplasia [9,10] and keratoconjunctivitis sicca [11,12] are other indications for ICS. A major advantage of ICS is the arrangement of harvested cells in their natural layout; thus enabling clinical pathologists to examine an exact copy of the area of interest.…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to what was found in the present study, Zuazo et al [22] found GCD of 497 cells/mm 2 in normal subjects and 310 cells/mm 2 in subjects with dry eyes, and Torricelli et al [4] found GCD of 521 cells/mm 2 in bulbar conjunctiva of normal subjects. Similarly, in a recent study conducted in India, Kumar et al [23] found GCD of 1462 cells/mm 2 in normal eyes. The lower GCD obtained in this study may be due to the fact that no pressure was applied during impression cytology process unlike those authors [4,23].…”
Section: Discussionmentioning
confidence: 80%
“…Similarly, in a recent study conducted in India, Kumar et al [23] found GCD of 1462 cells/mm 2 in normal eyes. The lower GCD obtained in this study may be due to the fact that no pressure was applied during impression cytology process unlike those authors [4,23]. In that way, only superficial layer(s) were removed and goblet cells in the deep layer may not be collected in the sample.…”
Section: Discussionmentioning
confidence: 80%
“…No contact lens induced dry eye studies from India were available for comparison. However dry eye studies done by Shah S et al (14 ) in Gujarat and Gupta N et al (15) in Delhi have found a greater prevalence of dry eye in females. Dry eye studies by Chia EM et al (16) have shown that females are 1.5 -2 times more likely to report dry eye symptoms compared to males.…”
Section: Discussionmentioning
confidence: 92%